The Role of SGLT2 Inhibitor on the Treatment of Diabetic Retinopathy - Wenjun Sha; Song Wen; Lin Chen; Bilin Xu; Tao Lei; Ligang Zhou (Journal of Diabetes Research)
Diabetic retinopathy (DR) is one of the most serious complications of diabetic microangiopathy. DR has an early onset and is not easy to detect. When visual impairment occurs, the optimal period for therapy is often missed. Therefore, the prevention and treatment of DR should start from the early stage of diabetes. Sodium-dependent glucose transporter 2 inhibitor (SGLT2i) is a new antidiabetic drug which is mainly used in clinical practice to control blood glucose of patients with type 2 diabetes prone to develop chronic heart failure. Recent studies have found that SGLT2 is also expressed in the human retina. Now, the prevention and treatment of diabetic retinopathy with SGLT2i while reducing blood sugar has become a new research field. Hence, this article reviewed the recent therapeutic and research progress of SGLT2 in the treatment of diabetic retinopathy.